Rethinking of identity under war: Pryazovia renaissance and regional centre ambitions in Mariupol before 2022 - Gnatiuk, Oleksiy; Mezentsev, Kostyantyn; Pidgrushnyi, Grygorii (Hungarian Geographical Bulletin, 2022)
The article addresses identity transformation in geopolitical fault-line city under a semi-frozen military conflict. Until 2014, the Donbas, a region in the eastern Ukraine, had a strong identity cultivated by the local industrial and financial groups. The Russian-backed military conflict induced rethinking of Donbas identity, giving a chance for revival of silenced regional identities. Our case study is Mariupol, the second most populous city in Donetsk oblast and the informal capital of Pryazovia that stepped out from the shadow of Donetsk. The research is based on the survey data (n = 1,251) collected in 2020 through personal interviews, analysed using descriptive statistics and binary logistic regression. The hypothesis that emerging Pryazovia identity should qualitatively differ from presumably stigmatized Donbas identity was confirmed only partially. The identity rethinking seems to be neither rapid no straightforward. Donbas identity appears quite persistent, while Pryazovia identity functions mainly as a complementary one. Instead of escape from the stigmatized Donbas identity, we observe rather its redefinition, including on local-centric (“Mariupolocentrism”) and Ukraine-centric bases.